Pressure sensor calibrations of acoustic telemetry transmitters. Issue 1 (December 2016) - Veilleux, Maxime; Lapointe, Nicolas; Webber, Dale; Binder, Tom; Blanchfield, Paul; Cruz-Font, Liset; Wells, Mathew; Larsen, Martin; Doka, Susan; Cooke, Steven
Abstract Background Acoustic transmitters are widely used to obtain information on the spatial ecology of fish and other aquatic animals. Some transmitters contain pressure sensors to estimate depth, which are factory-calibrated before being sold and have a specified range of error. Our goal was to assess the accuracy of these pressure sensors and the factory calibrations to assess whether researchers should conduct additional calibrations prior to use in the field. To evaluate error, we conducted calibrations on ten acoustic transmitters with pressure sensors (obtained from Vemco-Amirix Ltd.) both in the laboratory (pressure chambers at Hammond Bay Biological Station and Carleton University) and in the field (based on lowering tags to known depths in Toronto Harbour and Experimental Lakes Area). Slopes, intercepts, andR 2 values of researcher-calibrated sensors were compared to the factory-calibrated values to contrast calibration methods and identify directional biases. To estimate the effects of temperature on sensor performance, we calibrated the same sensors at varying temperatures and compared slopes, intercepts, and R2 values. Finally, we evaluated external effects (i.e., water temperature, salinity, and atmospheric pressure) on sensor output through simple modeling exercises to better understand potential sources of error. Results A significant difference was found among the slopes andR 2 values of the four calibration events, whereas no difference was found among the intercepts. There was also a significant effect of calibration water temperature on slopes, intercepts, andR 2 values. External effects should be taken into consideration when interpreting biological data as they have an effect on hydrostatic pressure thereby affecting the reported depths (1.77 m shallower to 6.47 m deeper than standard conditions). Conclusions Nonetheless, we did not find sufficient evidence to support the need for additional calibrations beyond those provided by the manufacturer as they did not markedly increase the accuracy of depth estimates.